2014
DOI: 10.1369/0022155414532655
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction Impairs Small Intestinal Mucosal Immunity in Neonatal Piglets

Abstract: SummaryIntrauterine growth restriction (IUGR) is a very common problem in both piglet and human neonate populations. We hypothesized that IUGR neonates have impaired intestinal mucosal immunity from birth. Using neonatal piglets as IUGR models, immune organ weights, the weight and length of the small intestine (SI), intestinal morphology, intraepithelial immune cell numbers, levels of cytokines and immunoglobulins, and the relative gene expression of cytokines in the SI were investigated. IUGR neonatal piglets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
71
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 35 publications
9
71
1
Order By: Relevance
“…Total RNA of the liver was extracted with Trizol reagents, and reverse transcription was conducted as described by Dong et al (2014). Briefly, after the RNA quality had been verified by a Thermo Fisher Scientific Nanodrop 2000 spectrophotometer (ratios of absorption including 260/280 nm and 260/230 nm between 1.90 and 2.05) and by agarose gel electrophoresis, 2 μg RNA were incubated at 72 °C with random primer (Promega, Belgium) for 5 min, then incubated for 1 hour with reverse transcription mixture (Takara, Dalian, China).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA of the liver was extracted with Trizol reagents, and reverse transcription was conducted as described by Dong et al (2014). Briefly, after the RNA quality had been verified by a Thermo Fisher Scientific Nanodrop 2000 spectrophotometer (ratios of absorption including 260/280 nm and 260/230 nm between 1.90 and 2.05) and by agarose gel electrophoresis, 2 μg RNA were incubated at 72 °C with random primer (Promega, Belgium) for 5 min, then incubated for 1 hour with reverse transcription mixture (Takara, Dalian, China).…”
Section: Methodsmentioning
confidence: 99%
“…All the data were processed with the student t-test of the SPSS statistical package (Version 20.0, SPSS Inc., Chicago, IL) as described by Dong et al (2014).Results were shown as mean ± SE. P value below 0.05 was regarded as significant.…”
Section: Methodsmentioning
confidence: 99%
“…CD4 + cells are T helper cells, which can produce cytokines and defend the host against extra-cellular microbes, while CD8 + cells are cytotoxic cells, which can recognize and kill host cells infected with intracellular microbes (Abbas et al, 1994). Our previous study has demonstrated that IUGR neonatal piglets exhibit a weaker cytokine secretion ability in the small intestines (Dong et al, 2014). We hypothesized this weaker secretion might be caused by the lower numbers of CD4 + and CD8 + lymphocytes in IUGR neonatal piglets.…”
Section: Introductionmentioning
confidence: 91%
“…The melt curves of a single gene in the different samples showed one single, overlapping peak, and the amplification efficiency of each of the target genes and the housekeeping gene were all similar and within a span of 0.9 and 1.1 (shown in Table 2). The relative gene expression levels were determined using Step-One software (Applied Bio-systems) and were calculated relative to the same gene in the duodenum of the NBW piglets using the 2 − CT method (Dong et al, 2014;Livak and Schmittgen, 2001).…”
Section: Fluorescence Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation